2021
DOI: 10.1186/s12974-021-02309-6
|View full text |Cite
|
Sign up to set email alerts
|

The semantics of microglia activation: neuroinflammation, homeostasis, and stress

Abstract: Microglia are emerging as critical regulators of neuronal function and behavior in nearly every area of neuroscience. Initial reports focused on classical immune functions of microglia in pathological contexts, however, immunological concepts from these studies have been applied to describe neuro-immune interactions in the absence of disease, injury, or infection. Indeed, terms such as ‘microglia activation’ or ‘neuroinflammation’ are used ubiquitously to describe changes in neuro-immune function in disparate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
198
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 347 publications
(200 citation statements)
references
References 235 publications
(324 reference statements)
2
198
0
Order By: Relevance
“…Intriguingly, these same studies found no differential expression of inflammation-associated molecules, suggesting that MDD is not marked by microglial ‘activation’ or neuroinflammation, but rather a more nuanced shift in microglial phenotype. This parainflammatory phenotype is observed in several models of chronic stress [36]. Given our data, it is interesting to speculate that microglial P2Y12 may play an important role in regulating synapse loss in MDD.…”
Section: Discussionsupporting
confidence: 66%
“…Intriguingly, these same studies found no differential expression of inflammation-associated molecules, suggesting that MDD is not marked by microglial ‘activation’ or neuroinflammation, but rather a more nuanced shift in microglial phenotype. This parainflammatory phenotype is observed in several models of chronic stress [36]. Given our data, it is interesting to speculate that microglial P2Y12 may play an important role in regulating synapse loss in MDD.…”
Section: Discussionsupporting
confidence: 66%
“…In addition to being first-line defenders in the CNS, these myeloid-derived cells are critical for homeostasis in the brain. They have inflammatory capabilities when activated, and produce IL-6 under inflammatory conditions [ 54 ]. Genes associated with microglial activation are upregulated in the postmortem ASD brain [ 55 , 56 , 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our ccl34b.1 + population (“amoeboid” cluster 1) likely corresponds to optic tectum-enriched neurogenic associated microglia (NAMs) and our ccl34b.1 - population (“ramified” cluster 4) likely corresponds to hindbrain-enriched synaptic-region associated microglia (SAMs) [62]. Separating microbial modulation of gene expression in distinct microglial functional subtypes enables us to identify homeostatic, neuroinflammatory, and parainflammatory effects of the microbiota [86]. In amoeboid cluster 1 NAMs the microbiota restrains expression of migration and chemotaxis genes while promoting expression of genes linked to lysosomal function, nucleotide metabolism, and mitochondrial function.…”
Section: Discussionmentioning
confidence: 99%